PENGARUH KUALITAS SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, KOMITMEN ORGANISASI, PERAN INTERNAL AUDIT DAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kota Dumai) - Rezky Safitri; Taufeni Taufik; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to analyze: 1) the effect of quality human resources on the quality of financial statements, 2) the effect of internal control systems on the quality of financial statements, 3) the effect of organizational commitment on the quality of financial statements, 4) the effect of the role of internal audit on the quality of financial statements, 5) the effect of regional financial management information system on the quality of financial statements. The population in this study was 30 OPD Dumai City. In this study, the sample used is the 90 respondents were selected using purposive sampling method. This study used primary data by dissemination of the questionnaires. Technical analysis for test hypothesis that used in this study are multiple linear regression analysis. The analytical tool used in this study was Stastistical Product and Service Solution (SPSS) version 20.0. The result of this research showed that : 1) quality of human resources affect on the quality of financial statements, 2) internal control system affect on the quality of financial statements, 3) organizational commitment affect on the quality of financial statements, 4) the role of internal control affect on the quality of financial statements, 5) regional financial management information system affect on the quality of financial statements.Keywords :Quality Human Resources, Internal Control Systems, Organizational Commitment, The Role of Internal Control, Regional Financial Management Information System